2022
DOI: 10.31234/osf.io/unbt7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitory Control and Alcohol Use History Predict Changes in Post-traumatic Stress Disorder Symptoms

Abstract: Post-traumatic stress disorder (PTSD) is a prevalent and disabling condition occurring frequently among Veterans. However, among those diagnosed with PTSD, predictors of changes in PTSD symptoms over time remain incompletely characterized. In the current study, we examined 187 post-9/11 Veterans (Mean baseline age = 32.8 years, 87% male) diagnosed with PTSD who participated in two extensive clinical and cognitive evaluations approximately two years apart. Our analyses focused on the association between baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The current study is part of an ongoing longitudinal study that has consistently found significant associations between PTSD/depressive symptoms and functional disability (Bernstein et al, 2022) as well as inhibitory control and PTSD (DeGutis et al, 2015;DeGutis et al, 2022).…”
Section: Sample Size Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is part of an ongoing longitudinal study that has consistently found significant associations between PTSD/depressive symptoms and functional disability (Bernstein et al, 2022) as well as inhibitory control and PTSD (DeGutis et al, 2015;DeGutis et al, 2022).…”
Section: Sample Size Justificationmentioning
confidence: 99%
“…With regard to PTSD, poorer predeployment inhibitory control ability on the go/no-go gradual-onset continuous performance task (gradCPT) has been associated with a greater likelihood of Veterans developing PTSD post-deployment (Samuelson et al, 2020). Inhibitory control abilities may allow individuals to disengage from or inhibit their responses to trauma-related triggers in their environment or memory, which may reduce the likelihood of developing more persistent PTSD symptoms (Aupperle et al, 2012;Catarino et al, 2015;DeGutis et al, 2022). Further, in those with PTSD, trauma-related or emotional stimuli may become considerably more salient and may overwhelm inhibitory control abilities (Ashley et al, 2013;Bardeen & Read, 2010), which could further exacerbate pre-existing inhibitory control deficits.…”
mentioning
confidence: 99%
“…For example, in a combat-exposed sample with and without PTSD, Karstoft et al (2013) identified four distinct trajectories: chronic (persistent symptoms), recovering (gradually declining symptoms), delayed onset (increase in symptoms following a delay), and resilience (initial low level of symptoms that remain low or subside). Though studies have looked at predictors of PTSD symptom changes (e.g., inhibitory control, DeGutis et al, 2023;depression, Sripada et al, 2017;alcohol abuse, Lee et al, 2020;executive functioning, Jagger-Rickels et al, 2022), factors that predict PTSD symptom changes require additional characterization. One model of PTSD suggests that variations in certain brain structures and functions may represent neurobiological vulnerabilities, pre-dating the trauma or development of PTSD (e.g., Admon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%